Edukasi Pola Hidup Bersih Dan Sehat Melalui Pelatihan Pembuatan Poster Pada Siswa SMAN 1 Dusun Utara Kabupaten Barito Selatan Tahun 2024 - Yulina Mingvianita; Endah Yusma Pratiwi; Syarah Veniaty; Jumadi Jumadi; Febriana Anti Rahayu; Via Veronica (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2025)
A clean and healthy lifestyle is the main foundation for building an optimal quality of life. One of the efforts intensively carried out by the government through the Ministry of Health is the Clean and Healthy Living Behavior Program (PHBS). In line with the goals of PHBS by the Ministry of Health, the implementation of a clean and healthy lifestyle is expected to raise awareness for the entire community (from various groups and ages) to create a clean and healthy environment. This awareness will lead Indonesian society to create a conducive environment, both for individuals, families, groups and communities. An educational alternative that can also train students' creativity and critical thinking skills to take part in clean and healthy living behavior programs, namely making educational posters in digital format. The aim of this community service activity is: a) to increase students' awareness about Clean and Healthy Lifestyles (PHBS), b) to increase students' knowledge and insight about Clean and Healthy Lifestyles (PHBS), c) to improve students' language skills in processing and conveying informative messages in a work, and d) to improve students' ability to master and utilize digital literacy. The method used in this service activity is a process method which includes three stages, namely; 1) preparation, 2) implementation and 3) evaluation. The results of this activity are 1) increasing students' knowledge and insight regarding Clean and Healthy Lifestyles (PHBS) and 2) increasing students' skills in processing and conveying informative messages in works in the form of digital posters.